2014
DOI: 10.1021/ie5012195
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Alkoxysilane Hydrolysis under Acidic Conditions by Fourier Transform Near Infrared Spectroscopy Combined with Partial Least-Squares Model

Abstract: Fourier transform near-infrared (FT-NIR) spectroscopy combined with a partial least-squares (PLS) model was successfully employed to study the hydrolysis kinetics of dimethyldiethoxysilane, methyltriethoxysilane, and tetraethoxysilane in an acid-catalyzed EtOH system. The high scanning speed and high sensitivity of FT-NIR spectroscopy enabled the new method to catch the rapid changes of the H2O and EtOH concentrations without delay, allowing the kinetic behaviors of the hydrolysis reactions of the specified al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 50 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…The rate constants could be in the ratio (4:3:2:1) [6], or they could have completely different values depending on the catalyst and solvent, as in the case of γ-glycidoxypropyltrimethoxysilane (GPS) [26]. Some articles, however, reported a single overall rate constant, k h , for the hydrolysis process [36,37].…”
Section: Hydrolysis and Early Stage Condensationmentioning
confidence: 99%
See 2 more Smart Citations
“…The rate constants could be in the ratio (4:3:2:1) [6], or they could have completely different values depending on the catalyst and solvent, as in the case of γ-glycidoxypropyltrimethoxysilane (GPS) [26]. Some articles, however, reported a single overall rate constant, k h , for the hydrolysis process [36,37].…”
Section: Hydrolysis and Early Stage Condensationmentioning
confidence: 99%
“…Different catalysts, such as ammonia, were used to improve the polymerization process to prepare monodisperse nanoparticles (Stöber method) [36,42,43,50,51,52]. Mineral acids, such as HCl [30,37,53,54,55,56,57,58], phosphoric acid [38], and hydrofluoric acid [59], as well as organic acids, such as acetic acid [2,23,26,45,60,61,62,63], chloroacetic acid [24], p -toluene sulphonic acid [22], and methane sulphonic acid [21], were also used. Researches also looked at the use of other organic compounds, such as tin alkyl esters [24,28], while boron-based catalysts were used to overcome the toxicity of the tin compounds.…”
Section: Hydrolysis and Early Stage Condensationmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are in line with previous reports on the determination of the activation energy and frequency factor of methyl triethoxysilane (MTES) in alkaline and acidic media. According to these reports, the activation energies are 50.09 and 97.84 kJ mol −1 in alkaline and acidic media, respectively . They also found that the activation energy and frequency factors decreased with decreasing the pH in an acidic medium …”
Section: Resultsmentioning
confidence: 92%
“…According to these reports, the activation energies are 50.09 and 97.84 kJ mol −1 in alkaline and acidic media, respectively . They also found that the activation energy and frequency factors decreased with decreasing the pH in an acidic medium …”
Section: Resultsmentioning
confidence: 92%